(3GdeNJUQ aj Yde GdYQhVs - (3CHh YHO Gddg Hf eMeO CHj LjT GdCfUGQj GdCfOdSjs
(3ChdgG (B:s
(3CMeO Gddg Ydi Cf bUO SdGeI GdWHY CeG HYO agPg cdeGJ dG jgLQgG EdG GdZHi eTcdGJ GdeNJUQ ai Yde GdYQhV s
(3BNQgG (B:s
(3hGeG Ydi GdCcKQi GdPi Ydjg LeghQ CQHGH gPG Gdaf aeaYhdGJ ef GdCLRGA GdCUhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg hbaI HGSe edG YHO Gddg GdYHOdi Ydi ChdGOg hjQLY JGQjNgG Edi SfI (B1239 (3g`s
(3HgJG Jedc HGSe YHO GdaJGM Hf MSf GdHQgjfi s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdeLGejYs